The Battles between Ramesses III and the “Sea-Peoples”: When, Where and Who? An Iconic Analysis of the Egyptian Reliefs - Evian, Shirly Ben-Dor (Zeitschrift für ägyptische Sprache und Altertumskunde, 2016)
While building on previous works by such scholars as Heinz and Spalinger, the article presents a new methodology specifically devised for the analysis of Egyptian war reliefs. The article contends that many historical reconstructions regarding the “Sea-Peoples” have ignored the basic principles of ancient Egyptian iconic art and preferred intuitive interpretations of the reliefs. This has led to historical misconceptions about the battles and aggressors. The new analysis provides a holistic reading of the reliefs within their context and is thereby able to present new insights as to the location of the battles and the nature of the “Sea-Peoples”.